The Interaction of Cellulose Thin Films With Small Organic Molecules—Comparability of Two Inherently Different Methods - Hoffellner, Lisa; Henögl, Elias M.; Petschacher, Patrick; Schennach, Robert; Leitner, Erich (Frontiers in Chemistry, 2021)
Paper is the material of choice for a large range of applications, because it has many favorable environmental and economic characteristics. Especially in the packaging sector of dry goods and food products, paper has found unique applications. For that purpose, it has to fulfill certain requirements, primarily it should protect the packaged goods. In order to ensure the compliance of a paper packaging, its interactions with the packaged goods should be investigated. Therefore, it is of utmost importance to understand how the paper interacts with chemicals of different nature and what factors influence these interactions; be that the nature of the paper or the characteristics of the substances. In this work, we investigated the surface interactions of cellulose thin films with n-decane and deuterated methanol using two different analytical methods, headspace solid phase microextraction with gas chromatography and flame ionization detection (HS-SPME-GC/FID) and temperature programmed desorption (TPD). Cellulose thin films were characterized with atomic force microscopy (AFM), contact angle and FTIR measurements and successfully applied as model systems for real paper samples. Regarding the interactions of the cellulose films with the model compounds, the two inherently different methods, HS-SPME-GC/FID and TPD, provide very comparable results. While the non-polar n-decane was readily released from the cellulose films, the polar model compound deuterated methanol showed a strong interaction with the polar cellulose surface.